Jump to navigation Jump to search

General

Display information for equation id:math.227089.1 on revision:227089

* Page found: Mixed radix (eq math.227089.1)

(force rerendering)

Cannot find the equation data in the database. Fetching from revision text.

Occurrences on the following pages:

Hash: 8bcf6166d995c4e5cf3a0c3b60a5c3d2

TeX (original user input):

 \sum_{i=0}^{n} (m_{i+1} - 1) \cdot M_i  = M_{n+1} - 1

TeX (checked):

\sum _{i=0}^{n}(m_{i+1}-1)\cdot M_{i}=M_{n+1}-1

LaTeXML (experimental; uses MathML) rendering

MathML (6.526 KB / 1.146 KB) :

i = 0 n ( m i + 1 - 1 ) M i = M n + 1 - 1 superscript subscript 𝑖 0 𝑛 subscript 𝑚 𝑖 1 1 subscript 𝑀 𝑖 subscript 𝑀 𝑛 1 1 {\displaystyle\sum_{{i=0}}^{{n}}(m_{{i+1}}-1)\cdot M_{i}=M_{{n+1}}-1}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle\sum_{{i=0}}^{{n}}(m_{{i+1}}-1)\cdot M_{i}=M_{{n+1}}-1}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.18" xref="p1.1.m1.1.18.cmml">
      <mrow id="p1.1.m1.1.18.1" xref="p1.1.m1.1.18.1.cmml">
        <mstyle displaystyle="true" id="p1.1.m1.1.18.1.1" xref="p1.1.m1.1.18.1.1.cmml">
          <munderover id="p1.1.m1.1.18.1.1a" xref="p1.1.m1.1.18.1.1.cmml">
            <mo largeop="true" movablelimits="false" symmetric="true" id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.2.1" xref="p1.1.m1.1.2.1.cmml">
              <mi id="p1.1.m1.1.2.1.1" xref="p1.1.m1.1.2.1.1.cmml">i</mi>
              <mo id="p1.1.m1.1.2.1.2" xref="p1.1.m1.1.2.1.2.cmml">=</mo>
              <mn id="p1.1.m1.1.2.1.3" xref="p1.1.m1.1.2.1.3.cmml">0</mn>
            </mrow>
            <mi id="p1.1.m1.1.3.1" xref="p1.1.m1.1.3.1.cmml">n</mi>
          </munderover>
        </mstyle>
        <mrow id="p1.1.m1.1.18.1.2" xref="p1.1.m1.1.18.1.2.cmml">
          <mrow id="p1.1.m1.1.18.1.2.1" xref="p1.1.m1.1.18.1.2.1.2.cmml">
            <mo stretchy="false" id="p1.1.m1.1.4" xref="p1.1.m1.1.18.1.2.1.2.cmml">(</mo>
            <mrow id="p1.1.m1.1.18.1.2.1.2" xref="p1.1.m1.1.18.1.2.1.2.cmml">
              <msub id="p1.1.m1.1.18.1.2.1.2.1" xref="p1.1.m1.1.18.1.2.1.2.1.cmml">
                <mi id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">m</mi>
                <mrow id="p1.1.m1.1.6.1" xref="p1.1.m1.1.6.1.cmml">
                  <mi id="p1.1.m1.1.6.1.1" xref="p1.1.m1.1.6.1.1.cmml">i</mi>
                  <mo id="p1.1.m1.1.6.1.2" xref="p1.1.m1.1.6.1.2.cmml">+</mo>
                  <mn id="p1.1.m1.1.6.1.3" xref="p1.1.m1.1.6.1.3.cmml">1</mn>
                </mrow>
              </msub>
              <mo id="p1.1.m1.1.7" xref="p1.1.m1.1.7.cmml">-</mo>
              <mn id="p1.1.m1.1.8" xref="p1.1.m1.1.8.cmml">1</mn>
            </mrow>
            <mo stretchy="false" id="p1.1.m1.1.9" xref="p1.1.m1.1.18.1.2.1.2.cmml">)</mo>
          </mrow>
          <mo id="p1.1.m1.1.10" xref="p1.1.m1.1.10.cmml"></mo>
          <msub id="p1.1.m1.1.18.1.2.2" xref="p1.1.m1.1.18.1.2.2.cmml">
            <mi id="p1.1.m1.1.11" xref="p1.1.m1.1.11.cmml">M</mi>
            <mi id="p1.1.m1.1.12.1" xref="p1.1.m1.1.12.1.cmml">i</mi>
          </msub>
        </mrow>
      </mrow>
      <mo id="p1.1.m1.1.13" xref="p1.1.m1.1.13.cmml">=</mo>
      <mrow id="p1.1.m1.1.18.2" xref="p1.1.m1.1.18.2.cmml">
        <msub id="p1.1.m1.1.18.2.1" xref="p1.1.m1.1.18.2.1.cmml">
          <mi id="p1.1.m1.1.14" xref="p1.1.m1.1.14.cmml">M</mi>
          <mrow id="p1.1.m1.1.15.1" xref="p1.1.m1.1.15.1.cmml">
            <mi id="p1.1.m1.1.15.1.1" xref="p1.1.m1.1.15.1.1.cmml">n</mi>
            <mo id="p1.1.m1.1.15.1.2" xref="p1.1.m1.1.15.1.2.cmml">+</mo>
            <mn id="p1.1.m1.1.15.1.3" xref="p1.1.m1.1.15.1.3.cmml">1</mn>
          </mrow>
        </msub>
        <mo id="p1.1.m1.1.16" xref="p1.1.m1.1.16.cmml">-</mo>
        <mn id="p1.1.m1.1.17" xref="p1.1.m1.1.17.cmml">1</mn>
      </mrow>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.18.cmml" xref="p1.1.m1.1.18">
        <eq id="p1.1.m1.1.13.cmml" xref="p1.1.m1.1.13"/>
        <apply id="p1.1.m1.1.18.1.cmml" xref="p1.1.m1.1.18.1">
          <apply id="p1.1.m1.1.18.1.1.cmml" xref="p1.1.m1.1.18.1.1">
            <csymbol cd="ambiguous" id="p1.1.m1.1.18.1.1.1.cmml" xref="p1.1.m1.1.18.1.1">superscript</csymbol>
            <apply id="p1.1.m1.1.18.1.1.2.cmml" xref="p1.1.m1.1.18.1.1">
              <csymbol cd="ambiguous" id="p1.1.m1.1.18.1.1.2.1.cmml" xref="p1.1.m1.1.18.1.1">subscript</csymbol>
              <sum id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1"/>
              <apply id="p1.1.m1.1.2.1.cmml" xref="p1.1.m1.1.2.1">
                <eq id="p1.1.m1.1.2.1.2.cmml" xref="p1.1.m1.1.2.1.2"/>
                <ci id="p1.1.m1.1.2.1.1.cmml" xref="p1.1.m1.1.2.1.1">𝑖</ci>
                <cn type="integer" id="p1.1.m1.1.2.1.3.cmml" xref="p1.1.m1.1.2.1.3">0</cn>
              </apply>
            </apply>
            <ci id="p1.1.m1.1.3.1.cmml" xref="p1.1.m1.1.3.1">𝑛</ci>
          </apply>
          <apply id="p1.1.m1.1.18.1.2.cmml" xref="p1.1.m1.1.18.1.2">
            <ci id="p1.1.m1.1.10.cmml" xref="p1.1.m1.1.10"></ci>
            <apply id="p1.1.m1.1.18.1.2.1.2.cmml" xref="p1.1.m1.1.18.1.2.1">
              <minus id="p1.1.m1.1.7.cmml" xref="p1.1.m1.1.7"/>
              <apply id="p1.1.m1.1.18.1.2.1.2.1.cmml" xref="p1.1.m1.1.18.1.2.1.2.1">
                <csymbol cd="ambiguous" id="p1.1.m1.1.18.1.2.1.2.1.1.cmml" xref="p1.1.m1.1.18.1.2.1.2.1">subscript</csymbol>
                <ci id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5">𝑚</ci>
                <apply id="p1.1.m1.1.6.1.cmml" xref="p1.1.m1.1.6.1">
                  <plus id="p1.1.m1.1.6.1.2.cmml" xref="p1.1.m1.1.6.1.2"/>
                  <ci id="p1.1.m1.1.6.1.1.cmml" xref="p1.1.m1.1.6.1.1">𝑖</ci>
                  <cn type="integer" id="p1.1.m1.1.6.1.3.cmml" xref="p1.1.m1.1.6.1.3">1</cn>
                </apply>
              </apply>
              <cn type="integer" id="p1.1.m1.1.8.cmml" xref="p1.1.m1.1.8">1</cn>
            </apply>
            <apply id="p1.1.m1.1.18.1.2.2.cmml" xref="p1.1.m1.1.18.1.2.2">
              <csymbol cd="ambiguous" id="p1.1.m1.1.18.1.2.2.1.cmml" xref="p1.1.m1.1.18.1.2.2">subscript</csymbol>
              <ci id="p1.1.m1.1.11.cmml" xref="p1.1.m1.1.11">𝑀</ci>
              <ci id="p1.1.m1.1.12.1.cmml" xref="p1.1.m1.1.12.1">𝑖</ci>
            </apply>
          </apply>
        </apply>
        <apply id="p1.1.m1.1.18.2.cmml" xref="p1.1.m1.1.18.2">
          <minus id="p1.1.m1.1.16.cmml" xref="p1.1.m1.1.16"/>
          <apply id="p1.1.m1.1.18.2.1.cmml" xref="p1.1.m1.1.18.2.1">
            <csymbol cd="ambiguous" id="p1.1.m1.1.18.2.1.1.cmml" xref="p1.1.m1.1.18.2.1">subscript</csymbol>
            <ci id="p1.1.m1.1.14.cmml" xref="p1.1.m1.1.14">𝑀</ci>
            <apply id="p1.1.m1.1.15.1.cmml" xref="p1.1.m1.1.15.1">
              <plus id="p1.1.m1.1.15.1.2.cmml" xref="p1.1.m1.1.15.1.2"/>
              <ci id="p1.1.m1.1.15.1.1.cmml" xref="p1.1.m1.1.15.1.1">𝑛</ci>
              <cn type="integer" id="p1.1.m1.1.15.1.3.cmml" xref="p1.1.m1.1.15.1.3">1</cn>
            </apply>
          </apply>
          <cn type="integer" id="p1.1.m1.1.17.cmml" xref="p1.1.m1.1.17">1</cn>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle\sum_{{i=0}}^{{n}}(m_{{i+1}}-1)\cdot M_{i}=M_{{n+1}}-1}</annotation>
  </semantics>
</math>

SVG (9.971 KB / 3.363 KB) :

sigma-summation Underscript i equals 0 Overscript n Endscripts left-parenthesis m Subscript i plus 1 Baseline minus 1 right-parenthesis dot upper M Subscript i Baseline equals upper M Subscript n plus 1 Baseline minus 1

MathML with SVG or PNG fallback (recommended for modern browsers and accessibility tools) rendering

MathML (0 B / 8 B) :

SVG image empty. Force Re-Rendering

SVG (0 B / 8 B) :


PNG (0 B / 8 B) :


Translations to Computer Algebra Systems

Translation to Maple

In Maple: sum((m[i + 1]- 1)* M[i], i = 0..n)= M[n + 1]- 1

Information about the conversion process:

I: You use a typical letter for a constant [the imaginary unit == the principal square root of -1].

We keep it like it is! But you should know that Maple uses I for this constant.

If you want to translate it as a constant, use the corresponding DLMF macro \iunit


\cdot: was translated to: *

i: the imaginary unit == the principal square root of -1 was translated to: i


Translation to Mathematica

In Mathematica: Sum[(Subscript[m, i + 1]- 1)* Subscript[M, i], {i, 0, n}]= Subscript[M, n + 1]- 1

Information about the conversion process:

I: You use a typical letter for a constant [the imaginary unit == the principal square root of -1].

We keep it like it is! But you should know that Mathematica uses I for this constant.

If you want to translate it as a constant, use the corresponding DLMF macro \iunit


\cdot: was translated to: *

i: the imaginary unit == the principal square root of -1 was translated to: i


Similar pages

Calculated based on the variables occurring on the entire Mixed radix page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results